2014
DOI: 10.18869/acadpub.jnms.1.3.32
|View full text |Cite
|
Sign up to set email alerts
|

Probability of obstructive sleep apnea in male patients with systolic heart failure and some related factors

Abstract: Background and Purpose: Sleep breathing disorders have a negative impact on the illness outcome and quality of life in patients with heart failure. This study was conducted to investigate the probability of obstructive sleep apnea in men with heart failure and some related factors. Method: This was a cross-sectional study conducted on 100 male patients with systolic heart failure selected through convenience sampling. Demographic data, anthropometric indices, and information about the disease, treatment, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The results of our study indicated that self-care behavior among participants is associated with certain factors, such as ethnicity, marital status, and body mass index (BMI). These findings align with a prior study that also identified ethnicity, marital status, and BMI as factors influencing self-care behavior in adults with hypertension (Ademe et al, 2019 ; Istek & Karakurt, 2016 ; Kharisna et al, 2018 ; Nakarmi et al, 2023 ; Zeighami Mohamadi et al, 2015 ). Self-care management for patients with hypertension involves adhering to lifestyle modification recommendations aimed at controlling risk factors that can exacerbate high blood pressure and worsen the patient’s hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study indicated that self-care behavior among participants is associated with certain factors, such as ethnicity, marital status, and body mass index (BMI). These findings align with a prior study that also identified ethnicity, marital status, and BMI as factors influencing self-care behavior in adults with hypertension (Ademe et al, 2019 ; Istek & Karakurt, 2016 ; Kharisna et al, 2018 ; Nakarmi et al, 2023 ; Zeighami Mohamadi et al, 2015 ). Self-care management for patients with hypertension involves adhering to lifestyle modification recommendations aimed at controlling risk factors that can exacerbate high blood pressure and worsen the patient’s hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Sexual satisfaction in Iran has always been ambiguous. On the other hand, studies in the eld indicate a progressive increase in the number of patients with chronic heart failure (5).For example, Zeyghami et al's study showed that 80% of systolic heart failure patients had ED (7). According to Zao et al's (2020) study(8), 38% of people with ED had cardiovascular disease, and ED predicted heart failure.…”
Section: Introductionmentioning
confidence: 99%